Influence of deposition temperature and precursor chemistry on the properties of atomic layer deposited Hf0.5Zr0.5O2 thin films - Seong Jae Shin; Hani Kim; Seungyong Byun; Jonghoon Shin; Jinwoo Choi; Suk Hyun Lee; Kyung Do Kim; Jae Hee Song; Dong Hoon Shin; Soo Hyung Lee; In Soo Lee; Hyunwoo Nam; et al. (Journal of Materiomics)
This study examined the effects of deposition temperature on Hf0.5Zr0.5O2 (HZO) thin films deposited using atomic layer deposition (ALD) with Tetrakis(ethylmethylamino) (TEMA) Hf, Zr, and cyclopentadienyl (CP)-linked Hf, Zr precursors. The discrete feeding method was utilized to stabilize the growth per cycle, addressing challenges related to CP-linked precursors' high viscosity and molecular mass. The ALD temperature windows for HfO2 and ZrO2 films using the CP-linked precursors were 330–370 °C and 290–330 °C, respectively, higher than those using the TEMA precursors (250–280 °C). Films deposited at higher temperatures with CP-linked precursors showed higher density and lower leakage currents than those with TEMA precursors, showing ferroelectric hysteresis loops from Hf0.5Zr0.5O2 (HZO) film at thicknesses as low as 5 nm without a wake-up process. In contrast, the film using TEMA precursor required a minimum thickness of 18 nm to exhibit similar properties. Crystallographic analysis revealed improved crystallization, larger grain sizes, and lower tensile stress in films deposited at higher temperatures. Also, in-situ crystallization was achievable for HZO films thicker than 6 nm when deposited at elevated temperatures. These findings demonstrate that higher temperature deposition by adopting CP-linked precursors enhances HZO thin film properties, making them suitable for advanced ferroelectric memory applications.